Study on Method of Doping Au Nanoparticles on ZnO Stratified Microstructure to Enhance Photocatalytic Ability and Antibacterial Activity - Anh Tuan Vu; Thi Anh Tuyet Pham (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
In this study, stratified microstructure gold/zinc oxide (Au/ZnO) composites were successfully prepared by the method of dispersing Au nanoparticles (Au NPs) on the surface of the hierarchical flower ZnO via HAuCl4 reduction in the presence of different reducing agents such as sodium citrate (SC), sodium borohydride (SB), sodium hydroxide and ethanol (SE), and Hg lamp 250W. Au-doped samples were named Au/ZnO-SC, Au/ZnO-SB, Au/ZnO-SE, and Au/ZnO-Hg lamp, respectively. Au/ZnO-SC and Au/ZnO-SB revealed the uniform distribution of Au nanoparticles on the ZnO substrate, meanwhile, Au nanoparticles were very densely distributed in Au/ZnO-SE and Au/ZnO-Hg lamp samples. The pure ZnO only showed an absorption peak in the ultraviolet (UV) region, Au/ZnO samples indicated additional absorption peaks in the visible light region (500-600 nm), which were characteristic of the surface plasmon resonance (SPR) effect of Au NPs in composites. Therefore, their bandgap energy was reduced compared to ZnO (3.202 eV), leading to increased photocatalytic efficiency under visible light irradiation. Among the doped samples, Au/ZnO-SC (with Au content as 5 wt%) had the largest surface area (26.23 m2/g) and the highest pore volume (0.263 cm3/g) and average pore width (33.2 nm). As a result, it showed the highest catalytic efficiency through complete degradation of tartrazine (TA) within 30 min with a reaction rate of 0.124 min−1 under Hg lamp 250 irradiation. In addition, both pure ZnO and Au/ZnO nanocomposites exhibited high antimicrobial activity in killing Escherichia coli (E. coli), and their enhancing effect of them was reliant on the weight ratio of Au on ZnO and the concentration of tested samples. These results indicated that Au/ZnO material has prominent potential for applications in water environment treatment. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).